Antithrombotic Treatments in Patients with Chronic Coronary Artery Disease or Peripheral Artery Disease: A Systematic Review of Randomised Controlled Trials - Rupert Bauersachs; Olivia Wu; Jean-Baptiste Briere; Kevin Bowrin; Katarzyna Borkowska; Anna Jakubowska; Vanessa Taieb; Mondher Toumi; Maria Huelsebeck (Cardiovascular Therapeutics)
Aims. Acetylsalicylic acid (ASA) is widely used for the prevention of atherothrombotic events in patients with chronic coronary artery disease (CAD) and peripheral artery disease (PAD), but the risk of vascular events remains high. We aimed at identifying randomised controlled trials (RCTs) on antithrombotic treatments in patients with chronic CAD or PAD. Methods. Searches were conducted on MEDLINE, EMBASE, and CENTRAL on March 1st, 2018. This systematic review (SR) uses a narrative synthesis to summarize the evidence for the efficacy and safety of antiplatelet and anticoagulant therapies in the population of both chronic CAD or PAD patients. Results. Four RCTs from 27 publications were included. Study groups included 15,603 to 27,395 patients. ASA alone was the most extensively studied (n=3); other studies included rivaroxaban with or without ASA (n=1), vorapaxar alone (n=1), and clopidogrel with (n=1) or without ASA (n=1). Clopidogrel alone and clopidogrel plus ASA compared to ASA presented similar efficacy with comparable safety profile. Rivaroxaban plus ASA significantly reduced the risk of the composite of cardiovascular death, myocardial infarction, and stroke compared to ASA alone, although major bleeding with rivaroxaban plus ASA increased. Conclusion. There is limited and heterogeneous evidence on the prevention of atherothrombotic events in patients with chronic CAD or PAD. Clopidogrel alone and clopidogrel plus ASA did not demonstrate superiority over ASA alone. A combination of rivaroxaban plus ASA may offer significant additional benefit in reducing cardiovascular outcomes, yet it may increase the risk of bleeding, compared to ASA alone.